2020
DOI: 10.1136/annrheumdis-2020-eular.4380
|View full text |Cite
|
Sign up to set email alerts
|

Sat0551 whole Body Macrophage Pet Imaging That Includes the Feet Can Provide Additional Information to Clinical Assessment in Patients With Early Rheumatoid Arthritis

Abstract: Background:Clinical assessment of arthritis is the cornerstone in the diagnosis and treatment of rheumatoid arthritis (RA). Nevertheless, reliable determination of (sub)clinical arthritis can be difficult, especially in the feet. Advanced imaging techniques may contribute to early diagnosis and therapy monitoring through sensitive detection and (quantitative) monitoring of synovitis. Previously, it has been demonstrated that macrophage imaging using (R)-[11C]PK11195 positron emission tomography (PET) allows fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…[21][22][23] Recently, our group demonstrated the additional value of quantitative assessment of macrophage imaging in RA as well as the value of imaging the feet for identifying clinical RA disease activity, as was prepublished in an abstract in the Annals of the Rheumatic Diseases. 30 In the present follow-up study, it is shown that this approach may also be useful at 2 weeks of treatment to predict therapy response at 13 weeks. However, the PET outcome measures found to be predictive in this proof-of-concept study differed when compared with previous research.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…[21][22][23] Recently, our group demonstrated the additional value of quantitative assessment of macrophage imaging in RA as well as the value of imaging the feet for identifying clinical RA disease activity, as was prepublished in an abstract in the Annals of the Rheumatic Diseases. 30 In the present follow-up study, it is shown that this approach may also be useful at 2 weeks of treatment to predict therapy response at 13 weeks. However, the PET outcome measures found to be predictive in this proof-of-concept study differed when compared with previous research.…”
Section: Discussionmentioning
confidence: 72%
“…In several previous studies, ( R )-[ 11 C]PK11195 targeting on PET/CT allowed for selective binding to (activated) macrophages in synovial tissue, providing a sensitive reflection of RA disease activity 21–23. Recently, our group demonstrated the additional value of quantitative assessment of macrophage imaging in RA as well as the value of imaging the feet for identifying clinical RA disease activity, as was prepublished in an abstract in the Annals of the Rheumatic Diseases 30. In the present follow-up study, it is shown that this approach may also be useful at 2 weeks of treatment to predict therapy response at 13 weeks.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations